Implications of age and country of membership in the relationship between perceived emotional support and depression: a cross-cultural study. - Riquelme Marín, Antonio; Martín Carbonell, Marta; Ortigosa Quiles, Juan-Manuel; Meda Lara, Rosa-Martha; Pérez Díaz, Raquel; López Navas, Ana I. (Anales de Psicología / Annals of Psychology, 2016)
The purpose of this study has been to analyze the implications that the age and the cultural factors associated with the nationality, to submit to the relationship between social support and depression. With this goal, has interviewed a total sample of 1503 persons of adult age (young people, adults and elderly) belonging to Spain, Cuba and Mexico. For the evaluation of the depression, has been used the questionnaire CES-D, while for the assessment of emotional support perceived and satisfaction with the same we applied a formal model of self-evaluation report prepared by us which gathers the perception of availability of emotional support from various sources (partner, family members, friends, colleagues, neighbors) and their satisfaction with the same. The results obtained indicate that the relationship obtained between emotional support according to different sources and values in depressive symptomatology is subject to changes depending on the cultural influences associated to the country of origin of those interviewed, and his age, as well as the interaction between both variables